Transforming our world literacy for sustainable development - Hanemann, Ulrike (UNESCO Institute for Lifelong Learning, 2015)
The literacy programmes featured in this publication are drawn from every region of the world and testify to the central role of literacy in responding to sustainable development challenges such as health, social equality, economic empowerment and environmental sustainability